Validation of Self-reported Periodontal Measures Among Health Professionals - Kaumudi J. Joshipura, BDS, SD; Waranuch Pitiphat, DDS; Chester W. Douglass, DMD, PhD (Blackwell Synergy, 2002)
The objective of this study was to determine the validity of self-reported periodontal measures among nondentist health professionals. Valid selfreported measures could provide a time- and cost-efficient alternative for large epidemiologic studies